Parenting Orphans Through the Lens of Tafsir Al-Misbah: A Case Study at An-Nur Orphanage, Medan - Mawarni, Agus; Nasution, Muhammad Ali Azmi (TAFSE: Journal of Qur'anic Studies, 2025)
This study explores the Qur’anic perspective on orphan care as articulated in Tafsir Al-Misbah by M. Quraish Shihab, and examines how these principles are reflected in the caregiving practices at An-Nur Orphanage, Medan. Employing a qualitative case study approach, data were collected through documentation, field observations, and in-depth interviews, and analyzed thematically and comparatively. The findings highlight four key principles emphasized in Tafsir Al-Misbah: compassion, gradual education, moral responsibility, and spiritual protection. These values are evident in An-Nur’s daily routines, educational programs, and the empathetic relationships between caregivers and children. However, the study also identifies obstacles, including limited professional human resources, the lack of tafsir-based training, and the absence of structured psychosocial strategies. This gap suggests a divergence between Qur’anic ideals and current institutional practices in Islamic orphan care. The results underscore the need to integrate Qur’anic values into orphanage policies and caregiver training programs. The novelty of this research lies in connecting thematic Qur’anic interpretation with empirical institutional analysis, offering a holistic and practical Islamic parenting model for orphans in today’s socio-religious context.